2007
DOI: 10.2174/138620707782507331
|View full text |Cite
|
Sign up to set email alerts
|

Functional Genomics and NMR Spectroscopy

Abstract: The recent success of the human genome project and the continued accomplishment in obtaining DNA sequences for a vast array of organisms is providing an unprecedented wealth of information. Nevertheless, an abundance of the proteome contains hypothetical proteins or proteins of unknown function, where high throughput approaches for genome-wide functional annotation (functional genomics) has evolved as the necessary next step. Nuclear magnetic resonance spectroscopy is playing an important role in functional ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 229 publications
(263 reference statements)
0
7
0
Order By: Relevance
“…335 Magnetic resonance imaging (MRI), or in vivo chemical shift imaging (a spectroscopic variant of MRI) has long been used to follow a host of diseases in animal models and humans in vivo, and this is an expanding field in drug discovery. 336,337 This provides advantages in human physiology as in vivo studies are closer to the observed phenotype than animal or tissue models. It also circumvents the need for quenching metabolism, and indeed from in vivo spectroscopic studies of brain metabolism one can determine that the intracellular concentration of lactate is B1 mM, compared with the 410 mM concentration detected in tissue extracts as a result of post mortem metabolism of glucose and glycogen.…”
Section: (Vii) Spatial Mapping Of Metabolite Distributions In Tissues...mentioning
confidence: 99%
“…335 Magnetic resonance imaging (MRI), or in vivo chemical shift imaging (a spectroscopic variant of MRI) has long been used to follow a host of diseases in animal models and humans in vivo, and this is an expanding field in drug discovery. 336,337 This provides advantages in human physiology as in vivo studies are closer to the observed phenotype than animal or tissue models. It also circumvents the need for quenching metabolism, and indeed from in vivo spectroscopic studies of brain metabolism one can determine that the intracellular concentration of lactate is B1 mM, compared with the 410 mM concentration detected in tissue extracts as a result of post mortem metabolism of glucose and glycogen.…”
Section: (Vii) Spatial Mapping Of Metabolite Distributions In Tissues...mentioning
confidence: 99%
“…Although the number of metabolites in a cell is usually one order lower compared with the number of genes or proteins, it is virtually impossible to simultaneously determine the complete metabolome with current technology. Mass spectrometry (MS) and nuclear magnetic resonance (NMR) are the most frequently used methods of detection in the analysis of the metabolome (Dunn, 2008;Powers, 2007). NMR is very useful in determining the structure of unknown compounds, but comes with the drawback of expensive instrumentation.…”
Section: The -Omes Of Systems Biologymentioning
confidence: 99%
“…To ensure that these analyses are accurate and unbiased, it is necessary to make as precise a prediction of the mass and retention time of a unknown metabolite as possible. This is essential to i ) the accuracy of compound recognition; ii ) the accurate calculation of chemical composition of a metabolite [9]; and iii ) the prediction of the function of unknown genes through metabolomics [8], [10], [11], [12], [13], [14].…”
Section: Introductionmentioning
confidence: 99%